How do collectives of amateurs handle complexity on financial markets while deciding? An ethnography of investment clubs - Welbers, Lydia Judith (Journal of Sociocybernetics, 2018)
This paper questions how investment clubs – as small groups of retail investors that pool their money – cope with issues of hyper-complexity and truth while deciding together where to invest their money. This may be challenging because investment-decisions are characterised by informational complexity, an unknown future and double contingency. By employing ethnographic data, this paper traces how investment clubs reach a collective decision despite hyper-complexity. It will be shown how the members of the group struggle to make sense of and to find a shared definition of a situation. During this process they try to reduce complexity by evaluating and deciding collectively. The ways the different groups achieve this is influenced by the group composition, their organisational structure and the interaction order. In some groups negotiations are an essential part of their meetings whereby complexity is initially cultivated. Negotiations are used to develop a shared definition of the situation. These groups question if the truth can be uncovered in financial markets. Other groups reduce complexity by using certain techniques to uncover the true value of a stock. These ways of coping with complexity are bound to certain ways of organising and types of members. Accordingly, successful evaluating and deciding, which means that decisions are made, is bound to several exclusions that are made legitimate by the inclusion in the financial market. In summary, the paper adds new insights to processes of decision making in situations that are characterised by complexity.